2004
DOI: 10.1002/mabi.200300094
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐Catalyzed Transformation of Poly(lactic acid) into Cyclic Oligomers

Abstract: Enzymatic transformations into cyclic oligomers were carried out with the objective of developing chemical recycling of poly(lactic acid)s, such as poly(D,L-lactic acid) (PDLLA), poly(D-lactic acid) (PDLA) and poly(L-lactic acid) (PLLA), which are typical biodegradable polymers. They were degraded by lipase in an organic solvent to produce the corresponding cyclic oligomer with a molecular weight of several hundreds. PDLLA (with a Mw of 84,000) was quantitatively transformed into cyclic oligomers by lipase RM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Poly(L-lactic acid) (PLLA) having an M w of 120 000 was transformed into cyclic oligomers by lipase CA at 100 • C. Similar results were obtained by the lipase-catalyzed degradation of poly(DL-lactic acid) (PDLLA). That is, PDLLA having an M w of 84 000 was quantitatively transformed into cyclic oligomers with the peaktop oligomerzation degree of the octamer (8-mer) by lipase RM at 60 • C. No linear-type fraction was detected in the MALDI-TOF mass spectrum [159].…”
Section: Lipase-catalyzed Transformation Of Biodegradable Polymers Inmentioning
confidence: 99%
“…Poly(L-lactic acid) (PLLA) having an M w of 120 000 was transformed into cyclic oligomers by lipase CA at 100 • C. Similar results were obtained by the lipase-catalyzed degradation of poly(DL-lactic acid) (PDLLA). That is, PDLLA having an M w of 84 000 was quantitatively transformed into cyclic oligomers with the peaktop oligomerzation degree of the octamer (8-mer) by lipase RM at 60 • C. No linear-type fraction was detected in the MALDI-TOF mass spectrum [159].…”
Section: Lipase-catalyzed Transformation Of Biodegradable Polymers Inmentioning
confidence: 99%
“…The treatment process by the activity of enzyme is under mild condition, regarding as a clean process, and does not contain any undesirable byproducts such as racemic of PLA after degradation. Poly(lactic acid) such as poly(DL-lactic acid), poly(D-lactic acid) and poly(L-lactic acid) were degraded by the activity of lipase in an organic solvent to produce cyclic oligomer with several enzyme for example, lipase RM (Lipozyme RM IM) and lipase CA (Novozym 435) at 60-100C (Takahashi et al, 2004). This report suggested that the cyclic oligomer might be suitable for repolymerization and recycling of PLA.…”
Section: Biological Recycling Of Plamentioning
confidence: 93%
“…So far, enzymatic polymer recycling in the presence of N-435 was conducted for: PLLA [103], PBA [104], PBS [104], PCL [105], PHB [106], poly(trimethylene carbonate) (PTMC) [107], PTCL [108], and in some cases the repolymerization step was also investigated [107].…”
Section: Degradation Of Aliphatic Polyestersmentioning
confidence: 99%
“…The systematic studies of Matsumura research group [103], showed that cyclic oligomers of l-lactide with a molar mass of several hundred, can be obtained in o-xylene solvent at 100 °C with 500 wt% of N-435. Much lower temperature of degradation was applied for poly(R,S)-3-hydroxybutanoate [106] and PCL [109], which were transformed into a reactive cyclic products in toluene, to give oligomers with M n less than 500 g mol −1 .…”
Section: Degradation Of Aliphatic Polyestersmentioning
confidence: 99%